2021
DOI: 10.1177/09526951211015886
|View full text |Cite
|
Sign up to set email alerts
|

Discourses on im/migrants, ethnic minorities, and infectious disease: Fifty years of tuberculosis reporting in the United Kingdom

Abstract: Ethnicity and im/migrant classification systems and their constituent categories have a long history in the construction of public health knowledge on tuberculosis in the United Kingdom. This article critically examines the categories employed and the epidemiological discourses on TB, im/migrants, and ethnic minorities in health reporting between 1965 and 2015. We employ a Sociology of Knowledge Approach to Discourse Analysis to trace the continuities and changes in the categories used and in the discursive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Infectious disease exposure in individuals with lower SES and minorities is not exclusive to COVID-19 ( 190 ). Studies have repeatedly demonstrated the disproportionate impact of tuberculosis ( 191 ), sexually transmitted diseases such as HIV/AIDS ( 192 ), and respiratory diseases ( 193 ) on these groups as well.…”
Section: The Microbiome and Infectious Diseasesmentioning
confidence: 99%
“…Infectious disease exposure in individuals with lower SES and minorities is not exclusive to COVID-19 ( 190 ). Studies have repeatedly demonstrated the disproportionate impact of tuberculosis ( 191 ), sexually transmitted diseases such as HIV/AIDS ( 192 ), and respiratory diseases ( 193 ) on these groups as well.…”
Section: The Microbiome and Infectious Diseasesmentioning
confidence: 99%